2017
DOI: 10.1111/acel.12659
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐scale comparative analysis of longevity genes and interventions

Abstract: SummaryHundreds of genes, when manipulated, affect the lifespan of model organisms (yeast, worm, fruit fly, and mouse) and thus can be defined as longevity‐associated genes (LAGs). A major challenge is to determine whether these LAGs are model‐specific or may play a universal role as longevity regulators across diverse taxa. A wide‐scale comparative analysis of the 1805 known LAGs across 205 species revealed that (i) LAG orthologs are substantially overrepresented, from bacteria to mammals, compared to the ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…In regard to this, it was previously suggested that upregulation of stress response genes could result in pro-longevity effects 18 . This is further supported by our previous study showing that overexpression of stress-related LAGs results in most cases in lifespan extension 27 . Remarkably, in the gray whale transcriptome, a great portion of the pro-longevity LAGs found through overexpression experiments (19 out of 30) are stress-related genes, which display expression values higher than average or median.…”
Section: Analysis Of Longevity-associated Genes (Lags) In the Gray Whsupporting
confidence: 87%
See 4 more Smart Citations
“…In regard to this, it was previously suggested that upregulation of stress response genes could result in pro-longevity effects 18 . This is further supported by our previous study showing that overexpression of stress-related LAGs results in most cases in lifespan extension 27 . Remarkably, in the gray whale transcriptome, a great portion of the pro-longevity LAGs found through overexpression experiments (19 out of 30) are stress-related genes, which display expression values higher than average or median.…”
Section: Analysis Of Longevity-associated Genes (Lags) In the Gray Whsupporting
confidence: 87%
“…A noteworthy finding is the lower than expected number of LAG homologues found both for anti-and prolongevity genes in the gray whale, particularly in view of the assumed high evolutionary conservation of LAGs 27 . This however has a technical explanation, namely the fact that the gray whale did not have a reference genome until now, and that the transcriptome analysis was performed de novo, whereas for model organisms, there are already numerous well annotated transcriptomes and genomes.…”
Section: Analysis Of Longevity-associated Genes (Lags) In the Gray Whmentioning
confidence: 84%
See 3 more Smart Citations